2022
DOI: 10.1063/5.0076029
|View full text |Cite
|
Sign up to set email alerts
|

Phase-averaged dynamics of a periodically surging wind turbine

Abstract: The unsteady power generation of a wind turbine translating in the streamwise direction is relevant to floating offshore wind turbines, kite-mounted airborne wind turbines, and other non-traditional wind-energy systems. To study this problem experimentally, measurements of torque, rotor speed, and power were acquired for a horizontal-axis wind turbine actuated in periodic surge motions in a fan-array wind tunnel at the Caltech Center for Autonomous Systems and Technologies (CAST). Experiments were conducted at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Dabiri (2020) recently relaxed that assumption and suggested that the contribution of an unsteady velocity potential could lead to theoretical efficiencies in excess of the so-called Betz limit. In parallel with this prediction, several studies have shown relative power enhancements over the steady operating power for turbines in surge motions or unsteady flows, both experimentally (Farrugia, Sant & Micallef 2014;El Makdah et al 2019;Mancini et al 2020;Wei & Dabiri 2022) and in simulations of varying fidelity (Farrugia, Sant & Micallef 2016;Wen et al 2017;Johlas et al 2021). However, the extent to which unsteady flow physics contributed to these observed power enhancements is unclear.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Dabiri (2020) recently relaxed that assumption and suggested that the contribution of an unsteady velocity potential could lead to theoretical efficiencies in excess of the so-called Betz limit. In parallel with this prediction, several studies have shown relative power enhancements over the steady operating power for turbines in surge motions or unsteady flows, both experimentally (Farrugia, Sant & Micallef 2014;El Makdah et al 2019;Mancini et al 2020;Wei & Dabiri 2022) and in simulations of varying fidelity (Farrugia, Sant & Micallef 2016;Wen et al 2017;Johlas et al 2021). However, the extent to which unsteady flow physics contributed to these observed power enhancements is unclear.…”
Section: Introductionmentioning
confidence: 79%
“…The model can therefore yield numerical predictions of the time-varying and time-averaged rotation rate, torque and power of a turbine under surge motions or dynamic inflow conditions. This stands in contrast to the linearized model developed by Wei & Dabiri (2022), which can be written as a transfer function for convenient analysis but is unable to capture changes in time-averaged quantities.…”
Section: A Nonlinear Model For Turbine Rotation Rate and Power Extrac...mentioning
confidence: 94%
See 3 more Smart Citations